“There is no carnival without samba”: Revealing barriers hampering biodiversity-based R&D and eco-design in Brazil - Charbel Jose Chiappetta Jabbour and Daniel Jugend and Ana Beatriz Lopes de Sousa Jabbour and Kannan Govindan and Devika Kannan and Walter Leal Filho (Journal of Environmental Management, 2018)
Considering the unique relevance of Brazilian biodiversity, this research aims to investigate the main barriers to biodiversity-based R&D and eco-design development in a leading national company which has been commended for its innovation and sustainability. The methodology for this research was based on on-location visits, in-depth interviews, and consensus building among R&D, sustainability, and quality managers. A multi-criteria decision-making (MCDM) approach was adopted through interpretive structural modelling (ISM), a method that assists decision makers to transform complex models with unclear data into structural models. Some of the most influential barriers to biodiversity-based eco-design initiatives are “lack of legal incentive”, “not enough demand from the market”, and “not enough available knowledge/scientific data.” The most relevant barrier was “no legal incentive” from government. Consequently, managers should concentrate their efforts in tackling those barriers that may affect other barriers known as ‘key barriers’. Government should work decisively toward promoting a framework of legal incentives for bio-based eco-design; otherwise, metaphorically, “there is not carnival without the samba singer who pushes the rhythm”. The results given here reveal the barriers for bio-based eco-design in a Brazilian leading company, and this is the first work combining ISM to barriers to biodiversity R&D and eco-design.